Spanish null subjects: descriptive and analytical issues - Fábregas, Antonio (Borealis – An International Journal of Hispanic Linguistics, 2025)
The goal of this article is to present a detailed overview of the empirical patterns concerning null subjects in Spanish, and the theories that have been proposed to account for them. After revising the syntactic, morphological and pragmatic aspects of the distinction between null and overt subjects in both main and subordinate clauses, the article discusses different approaches to (i) the nature of the null subject, (ii) the nature of the clausal property that makes them possible and (iii) the possible syntactic differences between null subjects and overt preverbal subjects.